2022
DOI: 10.3390/biomedicines10081896
|View full text |Cite
|
Sign up to set email alerts
|

Integration of miRNA:mRNA Co-Expression Revealed Crucial Mechanisms Modulated in Immunogenic Cancer Cell Death

Abstract: Immunogenic cell death (ICD) in cancer represents a functionally unique therapeutic response that can induce tumor-targeting immune responses. ICD is characterized by the exposure and release of numerous damage-associated molecular patterns (DAMPs), which confer adjuvanticity to dying cancer cells. The spatiotemporally defined emission of DAMPs during ICD has been well described, whereas the epigenetic mechanisms that regulate ICD hallmarks have not yet been deeply elucidated. Here, we aimed to examine the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…To address this, we conducted in vitro cytotoxicity assays using melanoma cell lines harboring either BRAF wild-type (WT) (SK-MEL-2) or BRAFV600E mutations (SK-MEL-28 and A375). These cell lines were exposed to various ICD inducers, including doxorubicin [20][21][22][23] and Me-ALA-based photodynamic therapy (PDT) [11], as well as a non-ICD inducer, cisplatin [24,25]. Across all treatments, dose-response curves demonstrated that the decrease in cell viability was directly proportional to the concentration of the respective drug used (Figure 2A-C).…”
Section: Impact Of Brafv600e Mutation On Sensitivity To Icd and Icd-a...mentioning
confidence: 99%
“…To address this, we conducted in vitro cytotoxicity assays using melanoma cell lines harboring either BRAF wild-type (WT) (SK-MEL-2) or BRAFV600E mutations (SK-MEL-28 and A375). These cell lines were exposed to various ICD inducers, including doxorubicin [20][21][22][23] and Me-ALA-based photodynamic therapy (PDT) [11], as well as a non-ICD inducer, cisplatin [24,25]. Across all treatments, dose-response curves demonstrated that the decrease in cell viability was directly proportional to the concentration of the respective drug used (Figure 2A-C).…”
Section: Impact Of Brafv600e Mutation On Sensitivity To Icd and Icd-a...mentioning
confidence: 99%